THE LEVEL OF FINANCIAL LITERACY AMONG MUSLIM MILLENNIAL STUDENTS - Bayram, Kamola; Olasubom, Salaudeen Salaudeen; Thartori, Voltisa (2021)
Millenials, also known as Generation Y, are a demographic cohort who were born between early 1980’s and late 1990’s and are reportedly to be active users of FinTech. At the same time, recent research documents the problems Millenials are prone to inadequate financial knowledge, an unsatisfactory current financial situation, and misuse of retirement accounts. The last segment is particularly very important since life expectancy today is rising, while pension and social welfare systems are being strained. In this paper we examine the level of financial literacy among millennial students who at the same time active users of financial technology. The data was collected via questionnaire distribution to International Islamic University Malaysia (IIUM) students in the campus. From all collected responses 217 which matches the research criteria such as students who belong to Millennial generation were selected for analysis. To measure financial literacy level, we use the “Big Three” method designed by Lusardi and Mitchell (2011). In our study where respondents are university students, findings suggest that 47% out of all 217 respondents has a satisfactory level of financial literacy. The level of financial literacy is higher among post-graduate students and engineering students. Mobile payment users comprise 64% of respondents and only 24% among them is financially literate. It is also noteworthy that 93% of respondents do not have a retirement account. These findings are very important since the study is conducted in a university environment where 100% of the respondents are involved in higher education. It is crucial to teach finance subjects in all faculties and there is a dire need to establish an institution which will regularly conduct a nationwide survey to access the level of financial literacy and financial behaviour of youth to avoid the financial collapse of Generation Y.